Protective role of oleic acid against palmitic acid-induced pancreatic fibrosis - Sonia Frendi; Anaïs Chassac; Killian Veron; Jérôme Raffenne; Rémy Nicolle; Miguel Albuquerque; Valérie Paradis; Anne Couvelard; Jérôme Cros; Vinciane Rebours (Journal of Translational Medicine)
Abstract Background Obesity has been associated with several pancreatic disorders and is an important risk factor for pancreatic cancer. Nevertheless, the role of lipids in the early steps of carcinogenesis is unknown. Although we previously identified two types of pancreatic fatty infiltration with different lipid compositions that were associated with precancerous lesions and fibrosis, their mechanisms of action have not been clarified. Methods We hypothesized that saturated palmitic acid and mono-unsaturated oleic acid (OA and PA) could play diverse roles in the activation of pancreatic stellate cells (PSCs) during the genesis of pancreatic fibrosis and the promotion of precancerous lesions. This study explored the lipotoxic effect of OA and PA on PSCs and exocrine pancreatic tissue (acinar cells). We also explored PA-induced pyroptosis in PSCs. A three-dimensional culture system of organotypic slices from human pancreatic tissues was used as well as a two-dimensional culture of hTERT immortalized PSCs. Results The results show that PA could induce the secretion of collagens and inflammatory cytokines (IL18) in PSCs (p < 0.05). We defined a standardized protocol of precision-cut pancreas slices cultured from human non-tumoral pancreatic tissue (n = 9). Both OA and PA are involved in the initiation of acinar cell transformation into ductal cells. OA was found to have a protective effect against PA-induced fibrosis (p < 0.05). Conclusion These results highlight the antagonistic roles of oleic and palmitic acids in the initiation of pancreatic fibrosis and show that palmitic acid has a profibrotic role.